Komponen Instrumen AKM Pada Proses Kognitif Soal AKM Literasi Membaca - Maharani Putri Kumalasani; Dian Fitri Nur Aini; Dian Ika Kusumaningtyas (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
In preparation for implementing the AKM, the teachers of SD Muhammadiyah 8 Malang City also prepared questions and deemed it necessary to pay close attention. Observations are carried out based on the components of the AKM question instrument that have been determined by the Ministry of Education and Culture. The method used is by examining and analyzing literacy AKM questions that have been prepared objectively and systematically. The source of the research data is the literacy AKM questions that have been made by the teacher. Data analysis was carried out regarding the suitability of the questions with the components of the AKM instrument on cognitive processes. This study aims to see how the questions that have been prepared by the teacher are in accordance with the components of the AKM instrument, especially in cognitive processes and see the quality of the questions. The results of the analysis related to the AKM questions that have been made by the teacher have a cognitive aspect instrument component at each grade level. Not all questions contain components of cognitive processing instruments. In addition, the forms of questions that have been made have different types of questions, namely multiple choice, short answers, true false, and so on.